SAÚDE DO TRABALHADOR RURAL: UM OLHAR ÀS CONDIÇÕES DE SAÚDE - MARCHI, DIONE D.; CASALINI, ELENISE; BATTISTI, IARA; REIS, MAGDA C. T.; MATTE, ROSANA; BIGOLIN, MONE E. (Salão do Conhecimento, 2013)
Resumo